Ion Charge States from a Global Time-dependent Wave-turbulence-driven Model of the Solar Wind: Comparison with in Situ Measurements - Pete Riley; Roberto Lionello; Yeimy J. Rivera (The Astrophysical Journal)
Solar wind charge-state measurements contain a wealth of knowledge related to the properties of the solar corona from where they originated. However, their interpretation has remained challenging because it convolves coronal temperature, density, and velocity along the particles’ trajectory through the corona before they “freeze in” and are convected outward through the solar wind. In this study, we calculate ion charge states by coupling a nonequilibrium ionization model with a global magnetohydrodynamic model of the corona and inner heliosphere. We present results for two periods characteristic of solar minimum and maximum and compare them with observations from the ACE spacecraft. We find that the model reproduces the essential features of the observations, rectifying an earlier inconsistency that was apparent in 1D calculations, and allows us to unambiguously trace the evolution of charge states from the base of the corona into the solar wind.